STRATEGI PENGUMPULAN PROGRAM GERAKAN KOIN NU (KOTAK INFAQ NAHDLATUL ULAMA) DI LAZISNU SINGGAHAN TUBAN - Sari, Innaka; Muchtharom, Moch. Zaenal Azis; Sifa, Moh. Agus (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2021)
The purpose of this study is to find out how the strategy for collecting and implementing the KOIN NU movement program at LAZISNU Singgahan. The research method is qualitative by using a field research approach through observation, documentation and interviews. From the results of this study, it can be seen that the strategies used by LAZISNU Singgahan in the success of the KOIN NU movement program are socialization, program implementation, building communication systems, service systems and bookkeeping in a clear and transparent manner. While the process in implementing or collecting the KOIN NU movement program, LAZISNU Singgahan carried out in three stages, the first was from LAZISNU sub-district distributing cans to each branch to be distributed to the community, either in groups or individually, the second was collecting cans in the community by the KOIN NU coordinator, the third is the counting and distribution of coins by the counting team.